Financial management and inflation - Bierman, Harold (New York : Free Press ; London : Collier Macmillan, 1981)
This book is the result of many conversations with executives where concerns with the impact of inflation on business affairs were expressed.
Includes bibliographical footnotes and index.
hza 27/08/2018
Loans
Keywords: Corporations; Accounting; Industrial management